2021
DOI: 10.1016/j.scitotenv.2021.145299
|View full text |Cite
|
Sign up to set email alerts
|

UV-A activation of peroxymonosulfate for the removal of micropollutants from secondary treated wastewater

Abstract: The occurrence of micropollutants (MPs) in the aquatic environment poses a threat for the environment and the human health. The application of advanced oxidation processes based in sulphate radicals (SR-AOPs) to eliminate these contaminants has attracted attention in recent years. In this work, the simultaneous degradation of 20 multi-class MPs (classified into 5 main categories, namely antibiotics, beta-blockers, other pharmaceuticals, pesticides, and herbicides) was evaluated for the first time in secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…However, in this work, it was observed that the application of a UV-A reactor achieved higher mineralization than the UV-C reactor. The activation of PMS with UV-A radiation was shown to be effective in the removal of micropollutants from the wastewater [67] and in the removal of organic carbon from WW [46], which is in agreement with the results obtained in this work. Although the photolysis of PMS is negligible with UV-A radiation [68], the application of Co 2+ appears to be the contributing factor that increased the efficiency of the reaction and higher mineralization of the organic carbon.…”
Section: Sr-aops Applied To a High Load Wwsupporting
confidence: 91%
“…However, in this work, it was observed that the application of a UV-A reactor achieved higher mineralization than the UV-C reactor. The activation of PMS with UV-A radiation was shown to be effective in the removal of micropollutants from the wastewater [67] and in the removal of organic carbon from WW [46], which is in agreement with the results obtained in this work. Although the photolysis of PMS is negligible with UV-A radiation [68], the application of Co 2+ appears to be the contributing factor that increased the efficiency of the reaction and higher mineralization of the organic carbon.…”
Section: Sr-aops Applied To a High Load Wwsupporting
confidence: 91%
“…Wastewater (WW) samples were collected from the secondary treatment tanks of an UWWTP located in northern Portugal. The characterization of this WW has already been reported in previous studies of our group [48,49]. The WW was filtered through 1.2 μm glass-fiber filters (47 mm GF/C, Whatman™, Maidstone, United Kingdom) to remove suspended solids and then frozen until usage.…”
Section: Adsorption Experiments With Wastewatermentioning
confidence: 99%
“…21 However, few studies simultaneously identified ROS generated during solar/PMS treatment and evaluated their contributions to organic pollutant removal. 31,32 In terms of practical application in water and wastewater treatment, the economic cost and optimal oxidant consumption have not been well documented. In addition, little work has been conducted to investigate toxicity of disinfection byproducts (DBPs) formed using solar/PMS as a pretreatment prior to final disinfection.…”
Section: Introductionmentioning
confidence: 99%